(3eQBI GdLfGf hYHQI GdjbXGfs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ CeG HYO MeOkG ddg GdehMO HGdGdgjI hGdceGd agPG cJGH dNUJg hGNJUQJg eeG PcQI Cgd GdJhGQjN GdSjO s
(3BNQgG (B:s
(3hGdMeO ddg GdPi HMeOg hHPcQg NJe GdcdGe hGHJOGFg JfGgi JGQjNi GdPi GfJbdJ eYXeg ef JGQjN GdPgHi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1647s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs